The influence of seeding rate and nitrogen on the development, yield components and yield of two wheat varieties - Maree, P. C. J.(Peter Charles John) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1964.